2006
DOI: 10.1111/j.1369-7625.2006.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of information in decision aids

Abstract: Objective We completed a systematic review of information reported as included in decision aids (DAs) for adult patients, to determine if it is complete, balanced and accurate.Search strategy DAs were identified using the Cochrane Database of DAs and searches of four electronic databases using the terms: Ôdecision aidÕ; shared decision makingÕ and ÔpatientsÕ; Ômultimedia or leaflets or pamphlets or videos and patients and decision makingÕ. Additionally, publications reporting DA development and actual DAs that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 166 publications
(73 reference statements)
5
70
0
5
Order By: Relevance
“…That analysis might find that a few items provide all that most recipients need, or that target audiences have such diverse information needs that they require different brief messages, or that there are too many critical facts for any brief message to suffice. Without analysis, though, one cannot know what content is adequate (61).…”
Section: Task 4: Evaluate Their Adequacy and Repeat As Necessarymentioning
confidence: 99%
“…That analysis might find that a few items provide all that most recipients need, or that target audiences have such diverse information needs that they require different brief messages, or that there are too many critical facts for any brief message to suffice. Without analysis, though, one cannot know what content is adequate (61).…”
Section: Task 4: Evaluate Their Adequacy and Repeat As Necessarymentioning
confidence: 99%
“…Decision support is a clinical skill whereby patients are provided with structured support during an explicit process of decision making that includes focused counseling, and in some cases employs a patient ''decision aid'' to enable them to make informed health care choices. [33][34][35] Patient decision aids are tools that help to clarify personal values and communicate information on the available options so that patients can make informed choices. Patient decision aids do not advise people to choose one option over another, nor are they meant to replace clinician consultation.…”
mentioning
confidence: 99%
“…They typically include relevant information about a particular decision as well as methods for clarifying and expressing the patient's values [2]. Many studies have demonstrated that decision aids are acceptable to patients, reduce uncertainty, assist people to clarify values and make decisions congruent with those values; assist those who are uncertain in making choices, reduce the time taken to make a decision and result in greater adherence to, and satisfaction with, the decision made [3,4].…”
Section: Introductionmentioning
confidence: 99%